1993
DOI: 10.1021/jm00069a012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of C-terminally truncated fragments of human-.alpha.-calcitonin gene-related peptide

Abstract: C-terminally truncated fragments of human alpha-calcitonin gene-related peptide (h-alpha-CGRP) were tested for their ability to stimulate amylase secretion from pancreatic acinar cells and relax precontracted mesenteric arteries. h-alpha-CGRP, h-alpha-CGRP (1-36), h-alpha-CGRP (1-35), and h-alpha-CGRP (1-34) were made by Merrifield's solid-phase peptide synthesis methodology. Peptides were purified by gel filtration, cation-exchange chromatography, and semipreparative reversed-phase high-performance liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
4
20
0
Order By: Relevance
“…6,17,18 A structure-activity profile for position 37 of h-R-CGRP is emerging in which a L-amino acid residue with a flexible side chain containing a phenyl ring and a C-terminal amide is required for highaffinity binding to CGRP1 receptors. The structureactivity profile is also consistent with structure-activity relationships of the C-terminal position reported for the smaller antagonist [Tyr 0 ]rat-R-CGRP (28)(29)(30)(31)(32)(33)(34)(35)(36)(37) 15 and the endogenous agonist h-R-CGRP. 29 This suggests that CGRP1 receptors have similar requirements of the C-terminal Phe residue for high-affinity binding of agonists and antagonists.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…6,17,18 A structure-activity profile for position 37 of h-R-CGRP is emerging in which a L-amino acid residue with a flexible side chain containing a phenyl ring and a C-terminal amide is required for highaffinity binding to CGRP1 receptors. The structureactivity profile is also consistent with structure-activity relationships of the C-terminal position reported for the smaller antagonist [Tyr 0 ]rat-R-CGRP (28)(29)(30)(31)(32)(33)(34)(35)(36)(37) 15 and the endogenous agonist h-R-CGRP. 29 This suggests that CGRP1 receptors have similar requirements of the C-terminal Phe residue for high-affinity binding of agonists and antagonists.…”
Section: Resultssupporting
confidence: 85%
“…It is of note that other workers found that acetylation of the amino terminus of h-R-CGRP (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), a shorter C-terminal fragment of h-R-CGRP that is also a weak antagonist, caused a 4-fold increase in antagonistic potency. 19 While no explanation was offered, this observation may also be due to increased stability of the N-terminal-acetylated peptide to aminopeptidase degradation.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations